Oracle HER2 Bond immunohistochemistry system validation - Nguyen, Trung (Journal of histotechnology, 2011)
The Leica Oracle human epidermal growth factor 2 (HER2) Bond immunohistochemistry (IHC) system is a fully automated testing kit available for the purpose of evaluating HER2 oncoprotein status of invasive breast tumors. This kit is compared to the existing technology of the DAKO antibody clone A0485 used within the Histology laboratory at Cabrini Hospital by way of a validation study on 80 archival breast tumor blocks and scored by a qualified pathologist not knowing the original HER2 status. The kit was firstly optimized for use at Cabrini's histology facility with consideration paid to tissue fixation protocols and antigen retrieval regimes using in-house tissue controls and cell line controls included in the kit. The overall concordance was low when the Oracle HER2 results were compared to the original DAKO HER2 results. Some of the reasons are a combination of over-retrieval of the HER2 antigen leading to overcalling HER2 scores in invasive breast cancers, scoring HER2 positivity in DCIS and benign lesions and not having access to the corresponding H&E slides when scoring HER2 immunohistochemistry. Also, HER2 immunohistochemistry is subject to a certain amount of bias when scoring. From 2010 onwards and before this study was completed, all invasive breast tumors now undergo HER2 in-situ hybridization studies regardless of the HER2 IHC result at Cabrini Hospital.